Pengaruh Substitusi Tepung Jamur Tiram Terhadap Tingkat Kekerasan dan Daya Terima Tepung Biskuit Ubi Jalar Ungu - Putri, Afika Iknar Wijaya (2016)
Vitamin A Deficiency (VAD) is a major nutritional problem in Indonesia. It is cause by inadequate intake of vitamin A and low protein status. Purple sweet potato flour has high content of beta-carotene and could be processed into biscuits product. Oyster mushroom flour could be used as is substituent of purple sweet potato flour to increase the protein content in biscuits.The purpose of this study was to determine the effect of oyster mushrooms flour substitution on hardness and acceptability of purple sweet potato biscuits.Completely randomized design was used in this research with 4 types of substitution treatments of oyster mushrooms flour, which were 10 %; 15 %; 20 % and 25 %. Data analysis of hardness and acceptability of purple sweet potato biscuits were statistically analyzed using one-way ANOVA and followed by Duncan at significance level of 95%.The results showed that there was a substitution effect of oyster mushroom flour to the level of violence purple sweet potato biscuits with a significance value of p = 0.001. The highest level of hardness shown by the substitution of 10% flour oyster mushrooms. There was a substitution effect of oyster mushroom flour to the acceptance of flavor, texture and overall with significant value respectively p = 0.001; p = 0.029; and p = 0.017. There is no substitution effect on the oyster mushroom flour color and flavor acceptability by the significant value of p = 0.703 and p = 0.069.Based on acceptability and hardness, it is recommended to use 10 % flour oyster mushrooms on purple sweet potato biscuits and analyze the effect of storability biscuit nutritional value and hardness for advanced research.